The Genetics and Genome-Wide Screening of Regrowth Loci, a Key Component of Perennialism in Zea diploperennis. Issue 5 (1st May 2019) - Ma, Anjun; Qiu, Yinjie; Raihan, Tajbir; Paudel, Bimal; Dahal, Subha; Zhuang, Yongbin; Galla, Aravind; Auger, Donald; Yen, Yang
Abstract: Perennialism is common among the higher plants, yet little is known about its inheritance. Previous genetic studies of the perennialism in Zea have yielded contradictory results. In this study, we take a reductionist approach by specifically focusing on one trait: regrowth (the plant's ability to restart a new life cycle after senescence on the same body). To address this, six hybrids were made by reciprocally crossing perennial Zea diploperennis Iltis, Doebley & R. Guzman with inbred lines B73 and Mo17 and Rhee Flint, a heirloom variety, of Z . mays L. ssp. mays . All the F1 plants demonstrated several cycles of growth, flowering, senescence and regrowth into normal flowering plants, indicating a dominant effect of the Z. diploperennis alleles. The regrowability ( i.e., the plants' ability to regrow after senescence) was stably transmitted to progeny of the hybrids. Segregation ratios of regrowth in the F2 generations are consistent with the trait controlled by two dominant, complementary loci, but do not exclude the influence of other modifiers or environment. Genome-wide screening with genotyping-by-sequencing technology indicated two major regrowth loci, regrowth 1 ( reg1 ) and regrowth 2 ( reg2 ), were on chromosomes 2 and 7, respectively. These findings lay the foundation for further exploration of the molecular mechanism of regrowth in Z. diploperennis . Importantly, our data indicate that there is no major barrier to transferring this trait into maize or other grass crops for perennial crop development with proper technology, which enhances sustainability of grain crop production in an environmentally friendly way.